Lyhyen terveyteen liittyvää elämänlaatua kartoittavan SF-20-mittarin validointi suomalaisessa aikuisväestössä - Aalto, Anna-Mari (Aiheita / Stakes, ISSN 1236-9845, 1997)
English summary: The validation of the SF-20 instrument for health related quality of life in the Finnish general population.
Keywords: Quality of Life; Health Status Indicators; Sickness Impact Profile; Self Concept; elämänlaatu; mittausmenetelmät; terveys; mittarit (mittaus); käsitykset; livskvalitet; mätmetoder; hälsa; mätare (mätning)